Związek wysokości z wybranymi cechami korony czteroletniej brzozy brodawkowatej (Betula pendula Roth) - Klepacki, Adam (Leśne Prace Badawcze, 2017)
This paper presents the results of an analysis on characteristics of birch crowns ( Betula pendula Roth) in relation to measures of the growth space occupied by a single tree at a young age. It also presents the relationships between the seedling height and certain crown characteristics. The study focused on four-year-old common birches growing in four different areas in the Elk Forest District in either fresh mixed coniferous or broadleaved forest. The measurements conducted on the chosen trees were used to calculate their crown characteristics such as crown diameter, length, height to the crown base, relative length and spread. They were also used to determine the growth characteristics of a single tree’s growth space, such as the crown area projected onto the ground, single tree space and the percentage use of unit area. Furthermore, fresh and dry leaf mass was determined. The birches growing in the fresh mixed coniferous forest reached an average height of 1.30 m, whereas in the fresh mixed broadleaved forest, the height of the trees was lower and amounted to 0.67 m. 95% of the trees had crown diameters of 0.57 m to 0.74 m in the fresh mixed coniferous forest, but only 0.19 m to 0.25 m in the fresh mixed broadleaved forest. The average lengths of the crowns in the fresh mixed coniferous and broadleaved forests amounted to 0.97 m and 0.37 m respectively. The author shows that there is a statistically significant correlation between the seedling height and the other examined characteristics. The best correlation was found between the height and the length of the crown (r=0.9858) for birches growing in the fresh mixed coniferous forest and between the height and single tree space (r=0.8468) for birches growing in the fresh mixed broadleaved forest.